Pengaruh Kualitas Layanan Elektronik, Harga Dan Pengalaman Pelanggan Terhadap Niat Beli Ulang Melalui Kepuasan Pelanggan Sebagai Variabel Intervening - Jati Saputro, Kevin Rangga; Supriyono, Supriyono; Utomo, Joko (JURNAL MANAJEMEN DAN BISNIS, 2025)
Objective – This study was conducted to analyze the influence of e-service quality, product price, and customer experience on repurchase intention through customer satisfaction among Tokopedia users in Kudus Regency. The research focused on digital marketing, specifically consumer behavior in the context of e-commerce. Novelty – This study's novelty lies in the use of customer satisfaction as an intervening variable. Method – A quantitative approach was employed by distributing questionnaires to 130 Tokopedia user respondents using a purposive sampling technique, namely those who had shopped on Shopee at least twice in the past three months. Data analysis was performed using the Structural Equation Modeling (SEM) method using AMOS. Finding – The results of this study indicate that e-service quality, product price, and customer experience have a positive and significant effect on customer satisfaction and repurchase intention. Furthermore, customer satisfaction has been shown to act as a mediating variable, strengthening the influence of e-service quality, product price, and customer experience on repurchase intention. Limitations and Implications– This study is limited and cannot be broadly generalized to other e-commerce platforms or different regions. Implications can be used as a basis for competitive pricing and creating a better customer experience to drive satisfaction and repurchase intention.